1994
DOI: 10.1080/00207599408246553
|View full text |Cite
|
Sign up to set email alerts
|

Imagery Value, Subjective and Objective Frequency, Date of Entry into the Language, and Degree of Polysemy in a Sample of 998 French Words

Abstract: A random sample of 998 lexical words was drawn from a dictionary of the French language. Two groups of subjects rated the words for imagery value (IV) and subjective frequency (SF). Despite substantial individual differences in the ratings, the subjective measures were highly reliable (α = 0.98 for both IV and SF). The relation between the standard deviation and the mean of the ratings can be described by a quadratic function (R = 0.93 for IV and R = 0.75 for SF). The independence of IV and frequency was confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
16

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 23 publications
(21 reference statements)
1
18
0
16
Order By: Relevance
“…A potential limitation in using the subjective frequency values reported by Flieller and Tournois (1994) is that their participants were not instructed to rate the words for frequency in print specifically. Therefore, the purpose of Experiment 5c was to examine further whether rime/body consistency affects subjective judgments of word frequency in printed materials.…”
Section: Experiments 5c: Does Fb Consistency Influence Frequency Judgmmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential limitation in using the subjective frequency values reported by Flieller and Tournois (1994) is that their participants were not instructed to rate the words for frequency in print specifically. Therefore, the purpose of Experiment 5c was to examine further whether rime/body consistency affects subjective judgments of word frequency in printed materials.…”
Section: Experiments 5c: Does Fb Consistency Influence Frequency Judgmmentioning
confidence: 99%
“…This approach was applied to a set of 122 monosyllabic French words for which subjective frequency was assessed by Flieller and Tournois (1994) using a seven-point scale. FB consistency values on rime/ body correspondences was given by LEXOP (Peereman & Content, 1998).…”
Section: Experiments 5c: Does Fb Consistency Influence Frequency Judgmmentioning
confidence: 99%
“…In the study on 1,493 monosyllabic French words, Ferrand et al (2008) found a significant inverse relationship between imageability and subjective frequency (r=-0.28; p<0.01). In a study of 998 lexical words randomly drawn from a French dictionary, Flieller and Tournois (1994) did not find any correlation (r=-0.01; p>0.05).…”
Section: Relationship Between Imageability and Frequencymentioning
confidence: 99%
“…Lexical databases have been established in some languages, most often English, for which databases exist on imageability, frequency, concreteness, familiarity, meaningfulness and age of acquisition (Paivio, Yuille & Madigan, 1968;Coltheart, 1981;Altarriba, Bauer and Benvenuto, 1999;Balota, Pilotti & Cortese 2001;Bird, Franklin & Howard 2001;Cortese & Khanna, 2008;Brysbaert, Warriner & Kuperman, 2014). Similar lexical data are also available for several other languages, such as Swedish (Blomberg & Öberg, 2015), Norwegian , Portuguese (Marques et al, 2007), Italian (Rofes, de Aguiar & Miceli, 2015), Dutch (Ghyselinck, De Moor & Brysbaert, 2000), and French (Flieller & Tournois, 1994). Some of these database are available online (e.g., Italian, Norwegian, Swedish) and some on paper (Dutch, English).…”
Section: Introductionmentioning
confidence: 99%
“…Of all the lexical charac-1995; Zeno, Ivenz, Millard, & Duvvuri, 1995;for Dutch, see, e.g., Baayen et al, 1995;for French, see, e.g., Lété, Sprenger-Charolles, & Colé, 2004;New, Pallier, Brysbaert, & Ferrand, 2004;for German, see, e.g., Baayen et al, 1995; for Greek, see, e.g., Ktori, van Heuven, & Pitchford, 2008; for Portuguese, see, e.g., Marques, Fonseca, Morais, & Pinto, 2007;for Spanish, see, e.g., Alameda & Cuetos, 1995;Sebastián-Gallés, Martí, Cuetos, & Carreiras, 2000). In comparison, the range of alphabetic languages for which subjective frequencies are available is limited (for English, see, e.g., Balota, Pilotti, & Cortese, 2001;Carroll, 1971;Shapiro, 1969;Tryk, 1968;for French, see, e.g., Bonin et al, 2003;Desrochers & Bergeron, 2000;Ferrand et al, 2008;Flieller & Tournois, 1994;Forget, 2005;Gonthier, Desrochers, Thompson, & Landry, 2009), as is the pool of words for which subjective frequency estimates are available in these languages. This imbalance may be attributed, in part, to the cost of collecting such ratings.…”
Section: Word Frequency As a Determinant Of Lexical Processingmentioning
confidence: 99%